Analgesic and anti-diarrheal activities of Aganosma dichotoma (Roth) K. Schum. in Swiss-albino mice model - Faruk, Md Al; Khan, Mohammad Firoz; Mian, Md Yeunus; Rahman, Mohammad Sharifur; Rashid, Mohammad A (Bangladesh Pharmaceutical Journal, 2015)
Aganosma dichotoma (Roth) K. Schum. is an indigenous plant of Bangladesh. Traditional healers use this plant to treat many diseases. In order to systematically explore the medicinal values of this plant, the crude methanol extract of leaves of A. dichotoma were screened for analgesic and antidiarrheal activities in mice model. The peripheral and central analgesic actions were determined by using acetic acid-induced writhing and tail immersion methods. The extract significantly (p < 0.05) attenuated the acetic acid-induced writhing in a dose dependent manner. A noticeable dose-dependent increase (p < 0.05) of latency period was also observed in the tail immersion method. In the castor oil induced anti-diarrheal assay, the extract exhibited significant (p < 0.05) anti-diarrheal effect at a dose of 400 mg/kg body weight. Bangladesh Pharmaceutical Journal 18(1): 15-19, 2015